Efektivitas Penggunaan Model PjBL terhadap Keaktifan Siswa pada Mata Pelajaran PKn Kelas II SD - Mayada, Tiara Liza; Sholicha, Asrilia Putri; Widodo, Susilo Tri; Azizah, Wulan Aulia; Wardanti, Tri Septianing (Peneliti.net, 2024)
This research is motivated by learning that is still centered on the teacher and the absence of an active attitude from students when learning takes place. The purpose of this study is to describe the effectiveness of using the PjBL model on grade II students in Civics subjects. The research method used is descriptive qualitative. The subjects in this study were grade II students of Candigaron 01 State Elementary School consisting of 12 students. The results showed the quality and effectiveness of learning when implementing PjBL. It can be concluded that the results of this study have increased from various aspects both from skills, attitudes, and knowledge. The results of this study are the value of skills with a percentage of 75%, 91% attitude, and 91% knowledge. The attitude aspect has the most significant results from other aspects with a percentage of 91%. The results of the attitude assessment shown by students using the PjBL model are able to make students active in the learning process. This activeness that students have is what supports students in the learning process.